Optimalisasi Preferensi Mahasiswa Dalam Pemilihan Laptop Menggunakan Metode TOPSIS - Erikasari, Vivie Zuliani; Zulaeha, Zulaeha; Mulqiya, Wafha Zahra; Maharani, Tyanshi Firli; Anshor, Abdul Halim (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
Students face challenges in choosing a laptop that suits their needs and budget due to the many features and specifications available in the market. To meet the needs of students, especially at Pelita Bangsa University, this research will analyze and develop a decision support system to select the right laptop. The preference ranking technique with similarity to the ideal solution (TOPSIS) method is used to evaluate and rank laptops based on important criteria such as price, performance, storage capacity, and portability. The results showed that the LENOVO THINKPAD E14 laptop brand became the top recommendation from the 15 laptop brands selected. It is expected that this system can assist students in making decisions about purchasing laptops that are more suitable for their academic needs and in accordance with their preferences.